The relationship between catheter-related bloodstream infection and multi-drug resistant bacteria: a five-year retrospective study - Juan Li; Yahua Zheng; Jingjing Ma; Yiqing Zhang; Hongyi Dong; Lijun Chen; Shunshun Lu; Shi Lu (BMC Infectious Diseases)
Abstract Background Catheter-related bloodstream infection (CRBSI) is a severe hospital-acquired infection primarily associated with using central venous catheters (CVCs). With the rise of antibiotic resistance and the emergence of multidrug-resistant organisms (MDROs), there is a growing concern about the relationship between MDROs and CRBSI. Objective To explore the association between MDROs and CRBSI. Methods A retrospective study was conducted on hospitalized patients with implanted CVCs over 54 months (January 2019 to June 2023). Results We included 50,718 patients with indwelling central venous catheters; 122 were diagnosed with central venous CRBSI) The incidence of CRBSI was 0.24% (122/50,718 patients). The rate of MDRO infections among non-CRBSI patients was only 3.86%, while the rate among CRBSI patients was 62.30% (χ² = 1065.80, p < 0.001). After excluding factors related to age, gender, medical history, environmental factors (ward of residence, length of hospitalization), catheter factors (catheter placement site, duration of catheterization, number of insertions), and other factors (duration of fever, abnormal white blood cell counts, frequency of mechanical ventilation) associated with CRBSI infection, the odds ratio for MDROs was 4.63 (95% CI: 2.86–7.50; P < 0.001; Fully adjusted model). Conclusion MDROs are independently associated with a higher incidence of CRBSI. These findings highlight the critical need for targeted infection control strategies against MDRO-associated CRBSI and formulate specific management strategies for these infections while promoting interdisciplinary collaboration to improve patient outcomes.